Expression and purification of thioredoxin-his 6-ZmDREB2.7 fusion protein in Escherichia coli for raising antibodies - Thuy Linh Nguyen; Thuy Duong Nguyen; Van Hai Nong; Thi Thu Hue Huynh (Vietnam Journal of Science, Technology and Engineering, 2019)
Dehydration-responsive element-binding (DREB) proteins play a critical role in the plant’s droughttolerance mechanism despite their presence in minor amounts in the cell. In this study, a maize-derived transcription factor protein, ZmDREB2.7, was overexpressed in the Escherichia coli strain Rosetta 1. The interested gene conjugating with the thioredoxin gene (TrxA) and his6 tag in the pET-32a vector encoded a 55.7 kDa fusion protein. The optimum condition for inducing the thioredoxin-his6-ZmDREB2.7 expression was five hours of induction with 0.05 mM IPTG at 30oC. The Tris-HCl 20 mM pH 8.0 lysis buffer was harnessed to extract the recombinant protein for the purification process. Using the immobilized-metal affinity chromatography column, the recombinant protein was purified and then injected into rabbits. The antisera containing polyclonal antibodies (pAbs) could specifically recognize the ZmDREB2.7 fusion protein. This study represents updated data on the bacterial expression of the recombinant ZmDREB2.7 protein and the production of anti-ZmDREB2.7 pAbs.